Exploring the Potential of Blockchain in Education - Sarah Ahmed (Global Journal of Multidisciplinary and Applied Sciences, 2023)
Blockchain technology, initially known for its application in cryptocurrency, is gaining traction in the education sector due to its promise of enhancing transparency, security, and efficiency in various educational processes. This paper explores the potential applications of blockchain technology in education, focusing on areas such as credentialing, student records management, and decentralized learning platforms. It discusses the benefits of blockchain, including its ability to reduce administrative burdens, prevent fraud, and provide students with greater control over their academic records. The study also examines the challenges and limitations of implementing blockchain in education, such as scalability, integration with existing systems, and regulatory concerns. The paper concludes by offering recommendations for educators, institutions, and policymakers on how to leverage blockchain to improve the educational experience and address key issues such as credential verification and data security.